Preparation method of high-toughness epoxy resin cross-linking for sports ice and snow equipment
Patent Information
- Application Number
- CN202611174412.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]针对现有冰雪器材用环氧树脂无法兼顾高低温力学性能、损伤可恢复性及批次稳定性的不足,本发明提供了一种体育冰雪器材用高强韧性环氧树脂交联制备方法
本发明采用反应型苯基硼酸二缩水甘油醚酯作为稀释剂,通过共价键接入环氧树脂三维交联网络,同时引入动态硼氧键结构,有效解决了现有技术中小分子稀释剂易迁移析出、交联网络不可逆导致低温脆性大、损伤无法恢复的缺陷。既避免了材料长期服役过程中稀释剂析出引发的力学性能持续衰减,又借助动态键的可逆作用实现受损后的性能自主恢复,显著提升材料的长期服役稳定性。
Smart Images

Figure CN122878593A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of epoxy resin crosslinking preparation technology, and in particular to a method for preparing high-strength and tough epoxy resin for sports and ice and snow equipment through crosslinking. Background Technology
[0002] The winter sports equipment industry has expanded rapidly in recent years, with increasing demands on the low-temperature mechanical properties, structural stability, and service life of matrix resins for load-bearing components such as the core layer of alpine skis and the body of ice hockey sticks. Epoxy resin has become the mainstream matrix material in this field due to its high mechanical strength and excellent bonding properties. The industry's core need is to prepare high-performance epoxy resin systems that simultaneously meet the requirements of low-temperature impact resistance, high-temperature stiffness retention, and damage recovery.
[0003] Currently, mainstream technologies fall into two categories. The first category involves a preparation system using general-purpose bisphenol A epoxy resin combined with small-molecule reactive diluents and fatty amine curing agents. Its working principle involves reducing the viscosity of the resin system through the small-molecule diluent to suit the molding process, followed by one-step isothermal curing to form a three-dimensional cross-linked network. This system is widely used in the production of low- to mid-range ice and snow equipment, with advantages including readily available raw materials, simple processes, and short curing cycles. However, this system has significant drawbacks: the small-molecule diluent is prone to migration and precipitation during long-term service, leading to a continuous decline in the material's mechanical properties; the cross-linked network is a completely irreversible structure, exhibiting high brittleness at low temperatures, easily cracking under strong impacts, and unable to recover its function, making it unsuitable for the demands of high-intensity ice and snow sports.
[0004] The second category is flexible segment modified epoxy resin systems. By introducing polyether or rubber-based flexible toughening components into the epoxy resin matrix, the segmental freedom of the crosslinked network is increased to improve low-temperature toughness. This system is currently used in some high-end ice and snow equipment products, with the advantage of significantly improved low-temperature impact resistance compared to general systems. However, this system still has shortcomings: ordinary flexible segments have a wide molecular weight distribution, easily leading to localized agglomeration in the matrix, causing stress concentration. While toughening, it significantly reduces the material's high-temperature stiffness. If additional dynamic covalent bonds are introduced to achieve repair functions, there are generally problems with easy hydrolysis of these dynamic bonds and poor service reliability. Furthermore, conventional isothermal or rapid curing processes are prone to uneven curing, resulting in large batch-to-batch performance fluctuations. Current technologies cannot simultaneously achieve the low-temperature high strength and toughness, high-temperature performance retention, damage recoverability, and service stability of epoxy resins used in ice and snow equipment, making it difficult to meet the actual needs of the high-end development of ice and snow sports equipment. Summary of the Invention
[0005] To address the shortcomings of existing epoxy resins for ice and snow equipment in simultaneously achieving high and low temperature mechanical properties, damage recoverability, and batch stability, this invention provides a method for crosslinking and preparing high-strength and tough epoxy resins for sports ice and snow equipment.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing a high-strength, high-toughness epoxy resin crosslinking material for sports and ice / snow equipment includes the following steps: S1: Synthesize diglycidyl ether phenylborate as a reactive diluent; S2: Mix phenylborate diglycidyl ether ester, bisphenol A epoxy resin E-51, and narrow molecular weight terminal hydroxyl polytetrahydrofuran evenly, stir and react at 85~95℃ for 2~2.5 hours, and add silane coupling agent 30 minutes before the end of the reaction. S3: Add alicyclic amine curing agent and accelerator to the prepolymerized system, stir and mix evenly, and then perform vacuum degassing treatment; S4: A three-stage gradient heating and curing process is adopted, with the heating rate strictly controlled at 1.8~2.2℃ / min. The first stage is held at 85~90℃ for 1.5~2 hours, the second stage is held at 125~135℃ for 2~2.5 hours, and the third stage is held at 155~165℃ for 2~2.5 hours. After the heating is completed, the temperature is allowed to drop naturally to room temperature to obtain epoxy resin material.
[0007] Furthermore, the synthesis steps of phenylboronic acid diglycidyl ether ester in S1 are as follows: phenylboronic acid and epichlorohydrin are mixed at a molar ratio of 1:2.1 to 1:2.3, and 0.3% to 0.5% of tetrabutylammonium bromide by total mass is added as a catalyst. The mixture is reacted at 70 to 90°C for 3 to 5 hours. After the reaction is completed, sodium hydroxide aqueous solution is added for neutralization. After separation, the organic phase is taken and the unreacted epichlorohydrin is removed by vacuum distillation. The epoxy equivalent of the obtained phenylboronic acid diglycidyl ether ester is 165 to 185 g / eq.
[0008] Furthermore, the mass proportions of each raw material in S2 are as follows: 100 parts of bisphenol A epoxy resin E-51, 14-20 parts of diglycidyl ether phenylborate, 18-22 parts of narrow molecular weight terminal hydroxyl polytetrahydrofuran, and 0.2-0.5 parts of silane coupling agent.
[0009] Furthermore, the molecular weight distribution coefficient of the narrow molecular weight terminal hydroxyl polytetrahydrofuran does not exceed 1.2, and the number average molecular weight is 600~900.
[0010] Furthermore, the stirring rate of the prepolymerization reaction in S2 is 300~500 rpm, the prepolymerization temperature is 85~95℃, the prepolymerization time is 2~2.5 hours, and the silane coupling agent is added 30 minutes before the end of the prepolymerization reaction.
[0011] Furthermore, the silane coupling agent is any one of KH550, KH560, or KH570.
[0012] Furthermore, the alicyclic amine curing agent in S3 is isophorone diamine, menthol diamine, or 1,3-cyclohexanedimethylamine, with an addition amount of 20-40 parts by weight, and the accelerator is 2,4,6-tris(dimethylaminomethyl)phenol, with an addition amount of 0.5-2 parts by weight.
[0013] Furthermore, in S3, the vacuum degree of vacuum degassing is -0.09MPa to -0.1MPa, the degassing temperature is 40 to 50℃, and the degassing time is 10 to 20 minutes.
[0014] Furthermore, the prepared epoxy resin material is used to prepare the core layer of alpine skis or the body components of ice hockey sticks, wherein the epoxy resin material has an impact strength ≥50kJ / m at -40℃. 2 Fracture toughness ≥7.5MPa·m 1 / 2 Tensile strength ≥105MPa, and impact strength recovery rate ≥85% after heating at 80℃ for 1 hour.
[0015] The present invention has the following beneficial effects: This invention uses reactive diglycidyl phenylborate as a diluent, which is covalently integrated into the three-dimensional cross-linked network of epoxy resin. Simultaneously, a dynamic boron-oxygen bond structure is introduced, effectively solving the defects of existing technologies, such as easy migration and precipitation of small-molecule diluents, irreversible cross-linking leading to high low-temperature brittleness, and irreversible damage. This not only avoids the continuous degradation of mechanical properties caused by diluent precipitation during long-term service but also enables self-recovery of performance after damage through the reversible effect of dynamic bonds, significantly improving the long-term service stability of the material.
[0016] This invention employs terminally hydroxyl polytetrahydrofuran with a narrow molecular weight distribution as a toughening component. By precisely controlling the dispersion state of flexible segments in the crosslinked network, it effectively solves the defects of ordinary flexible toughening components in the prior art, such as easy agglomeration leading to stress concentration and reduced high-temperature stiffness of materials while toughening. It significantly improves the low-temperature impact toughness of epoxy resin while maintaining the structural rigidity of the matrix and the retention rate of high-temperature mechanical properties, thus ensuring service adaptability in both high and low temperature environments.
[0017] This invention employs a three-stage gradient heating and curing process with strictly controlled heating rates. By adjusting the crosslinking reaction rate and network molding uniformity in stages, it effectively solves the defects of uneven crosslinking and large batch-to-batch performance fluctuations caused by unreasonable curing processes in existing technologies. It ensures the uniformity and batch consistency of the crosslinked network structure, effectively reducing performance deviations between different batches and improving the yield of large-scale production. The epoxy resin material prepared by this invention is suitable for the production needs of various load-bearing components in snow sports, such as the core layer of alpine skis and the body of ice hockey sticks. It can cover the performance requirements of different levels of professional snow sports equipment and can achieve large-scale production without significant modifications to existing molding production lines, possessing high industry promotion value. Attached Figure Description
[0018] Figure 1 This is a flowchart of a method for preparing high-strength and tough epoxy resin crosslinking for sports ice and snow equipment proposed in this invention; Figure 2 This is a bar chart comparing the low-temperature mechanical properties of typical samples proposed in this invention. Figure 3 This is a line graph showing the retention rate of impact strength during damp heat aging proposed in this invention. Figure 4 This is a bar chart comparing the impact strength dispersion of multiple production batches proposed in this invention. Figure 5 This is a bar chart comparing the self-repair efficiency of different damage levels proposed in this invention. Figure 6 This is a line graph showing the relationship between the amount of reactive diluent added and the core performance proposed in this invention. Detailed Implementation
[0019] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0020] All mechanical property tests were conducted in accordance with the corresponding national standards: impact strength test according to GB / T 1843-2008, tensile strength test according to GB / T 1040.1-2025, fracture toughness test according to GB / T 4161-2007, and damp heat aging test according to GB / T 2573-2008.
[0021] Explanation of the reaction principle The synthesis reaction formula of phenylboronic acid and epichlorohydrin is as follows: C6H5B(OH)2+2C3H5ClO→C6H5B[OCH2CH(OH)CH2Cl]2 C6H5B[OCH2CH(OH)CH2Cl]2+2NaOH→C6H5B(OCH2CH(O)CH2)2+2NaCl+ 2H2O The phenylboronic acid diglycidyl ether ester prepared by this reaction has both epoxy end groups that can participate in crosslinking and dynamic boron-oxygen bond structure. It avoids the migration and precipitation of diluent by covalently connecting to the crosslinking network, and achieves damage repair by reversible exchange of boron-oxygen bonds, thus solving the defects of existing technology such as easy migration of diluent and irreversible crosslinking network.
[0022] The narrow molecular weight terminal hydroxyl polytetrahydrofurans used in the examples are custom-grade narrow distribution PTMEG (acid-stable type, referencing BASF PolyTHF S series product standards), including: number average molecular weight 650: molecular weight distribution 1.12, number average molecular weight 750: molecular weight distribution 1.14, number average molecular weight 850: molecular weight distribution 1.15, all with molecular weight distribution coefficients below 1.2. Example 1
[0023] S1: Phenylboronic acid and epichlorohydrin were mixed at a molar ratio of 1:2.1, and 0.3% tetrabutylammonium bromide was added as a catalyst. The mixture was reacted at 70℃ for 5 hours. After the reaction was completed, 10% sodium hydroxide aqueous solution was added to neutralize the mixture. After separation, the organic phase was subjected to vacuum distillation at 120℃ and -0.1MPa to remove unreacted epichlorohydrin. The measured epoxy equivalent of the obtained diglycidyl ether phenylboronic acid was 166 g / eq, and the theoretical boron content was 4.28 wt%, while the measured value was 4.21 wt%, with a deviation of less than 1.7%. S2: Take 100 parts by weight of bisphenol A epoxy resin E-51, 14 parts of the above-prepared phenylboronic acid diglycidyl ether ester, and 18 parts of PolyTHF 650 S and mix them evenly. Control the stirring speed at 300 rpm and the reaction temperature at 85℃. After the prepolymerization reaction is completed for 1.5 hours, add 0.2 parts of silane coupling agent KH550 and continue the reaction for another 0.5 hours. The total prepolymerization time is 2 hours.
[0024] S3: Add 20 parts of isophorone diamine and 0.5 parts of accelerator 2,4,6-tris(dimethylaminomethyl)phenol to the prepolymerized system, stir and mix evenly, and then degas under vacuum at 40℃ and -0.095MPa for 15 minutes.
[0025] S4: Control the heating rate at 1.8℃ / min and use a three-stage gradient heating and curing method: the first stage is to heat to 85℃ and hold for 2 hours, the second stage is to heat to 125℃ and hold for 2.5 hours, the third stage is to heat to 155℃ and hold for 2.5 hours, and after the holding period, the temperature is allowed to drop naturally to room temperature to obtain epoxy resin material.
[0026] The sample prepared in this embodiment has the following properties: impact strength at -40℃ 52.3 kJ / m 2 Tensile strength 108.2 MPa, fracture toughness 7.7 MPa·m 1 / 2 The impact strength retention rate was 91.2% after aging at 85℃ / 85%RH for 500 hours and 86.4% after 1000 hours. In the self-healing experiment, the sample was subjected to a 50J hammer impact, which caused visible cracks but not complete fracture. The damaged sample was then placed in an 80℃ constant temperature oven and heated for 1 hour. The impact strength recovery rate was 86.1%. Example 2
[0027] S1: Phenylboronic acid and epichlorohydrin were mixed at a molar ratio of 1:2.2, and 0.4% tetrabutylammonium bromide was added as a catalyst. The mixture was reacted at 80°C for 4 hours. After the reaction was completed, 10% sodium hydroxide aqueous solution was added to neutralize the mixture. After separation, the organic phase was distilled under reduced pressure at 120°C and -0.1 MPa to remove unreacted epichlorohydrin. The measured epoxy equivalent of the obtained diglycidyl ether phenylboronic acid was 175 g / eq, and the theoretical boron content was 4.28 wt%, while the measured value was 4.25 wt%, with a deviation of less than 0.7%.
[0028] S2: Take 100 parts by weight of bisphenol A epoxy resin E-51, 17 parts of the above-prepared phenylboronic acid diglycidyl ether ester, and 20 parts of PolyTHF 750 S and mix them evenly. Control the stirring speed at 400 rpm and the reaction temperature at 90℃. After the prepolymerization reaction is 1.75 hours, add 0.35 parts of silane coupling agent KH560 and continue the reaction for 0.5 hours. The total prepolymerization time is 2.25 hours.
[0029] S3: Add 30 parts of menthol diamine and 1.2 parts of accelerator 2,4,6-tris(dimethylaminomethyl)phenol to the prepolymerized system, stir and mix evenly, and then degas under vacuum at 45℃ and -0.098MPa for 15 min.
[0030] S4: Control the heating rate to 2.0℃ / min and use a three-stage gradient heating and curing method: the first stage is to heat to 88℃ and hold for 1.75 hours, the second stage is to heat to 130℃ and hold for 2.25 hours, the third stage is to heat to 160℃ and hold for 2.25 hours, and after the holding period, the temperature is allowed to drop naturally to room temperature to obtain epoxy resin material.
[0031] The sample prepared in this embodiment has the following properties: impact strength at -40℃ 56.7 kJ / m 2 Tensile strength 112.4 MPa, fracture toughness 8.2 MPa·m 1 / 2 The impact strength retention rate was 93.5% after aging at 85℃ / 85%RH for 500 hours and 88.7% after 1000 hours. In the self-healing experiment, the sample was subjected to a 50J hammer impact, which caused visible cracks but not complete fracture. The damaged sample was then placed in an 80℃ constant temperature oven and heated for 1 hour. The impact strength recovery rate was 89.3%. Example 3
[0032] S1: Phenylboronic acid and epichlorohydrin were mixed at a molar ratio of 1:2.3, and 0.5% of tetrabutylammonium bromide was added as a catalyst. The mixture was reacted at 90°C for 3 hours. After the reaction was completed, 10% sodium hydroxide aqueous solution was added to neutralize the mixture. After separation, the organic phase was distilled under reduced pressure at 120°C and -0.1 MPa to remove unreacted epichlorohydrin. The measured epoxy equivalent of the obtained diglycidyl ether phenylboronic acid was 184 g / eq, and the theoretical boron content was 4.28 wt%, while the measured value was 4.23 wt%, with a deviation of less than 1.2%.
[0033] S2: Take 100 parts by weight of bisphenol A epoxy resin E-51, 20 parts of the above-prepared phenylboronic acid diglycidyl ether ester, and 22 parts of PolyTHF 850 S and mix them evenly. Control the stirring speed at 500 rpm and the reaction temperature at 95℃. After 2 hours of prepolymerization, add 0.5 parts of silane coupling agent KH570 and continue the reaction for 0.5 hours. The total prepolymerization time is 2.5 hours.
[0034] S3: Add 40 parts of isophorone diamine and 2 parts of accelerator 2,4,6-tris(dimethylaminomethyl)phenol to the prepolymerized system, stir and mix evenly, and then degas under vacuum at 50℃ and -0.1MPa for 20 min.
[0035] S4: Control the heating rate at 2.2℃ / min and use a three-stage gradient heating and curing method: the first stage is to heat to 90℃ and hold for 1.5 hours, the second stage is to heat to 135℃ and hold for 2 hours, the third stage is to heat to 165℃ and hold for 2 hours, and after the holding period, the temperature is allowed to drop naturally to room temperature to obtain epoxy resin material.
[0036] The sample prepared in this embodiment has the following properties: impact strength at -40℃ 54.1 kJ / m 2 Tensile strength: 109.7 MPa; Fracture toughness: 7.9 MPa·m 1 / 2The impact strength retention rate was 92.1% after aging for 500 hours at 85℃ / 85%RH and 87.3% after 1000 hours. In the self-healing experiment, the sample was subjected to a 50J hammer impact, which caused visible cracks but not complete fracture. The damaged sample was then placed in an 80℃ constant temperature oven and heated for 1 hour. The impact strength recovery rate was 87.5%. Example 4
[0037] S1: Phenylboronic acid and epichlorohydrin were mixed at a molar ratio of 1:2.1, and 0.3% of tetrabutylammonium bromide was added as a catalyst. The mixture was reacted at 70°C for 5 hours. After the reaction was completed, 10% sodium hydroxide aqueous solution was added to neutralize the mixture. After separation, the organic phase was distilled under reduced pressure at 120°C and -0.1 MPa to remove unreacted epichlorohydrin. The measured epoxy equivalent of the obtained diglycidyl ether phenylboronic acid was 167 g / eq, and the measured boron content was 4.22 wt%.
[0038] S2: Take 100 parts by weight of bisphenol A epoxy resin E-51, 15 parts of the above-prepared phenylboronic acid diglycidyl ether ester, and 19 parts of PolyTHF 650 S and mix them evenly. Control the stirring speed at 300 rpm and the reaction temperature at 85℃. After the prepolymerization reaction is completed for 1.5 hours, add 0.2 parts of silane coupling agent KH560 and continue the reaction for another 0.5 hours. The total prepolymerization time is 2 hours.
[0039] S3: Add 22 parts of isophorone diamine and 0.5 parts of accelerator 2,4,6-tris(dimethylaminomethyl)phenol to the prepolymerized system, stir and mix evenly, and then degas under vacuum at 40℃ and -0.095MPa for 15 min.
[0040] S4: Control the heating rate at 1.8℃ / min and use a three-stage gradient heating and curing method: the first stage is to heat to 85℃ and hold for 2 hours, the second stage is to heat to 125℃ and hold for 2.5 hours, the third stage is to heat to 155℃ and hold for 2.5 hours, and after the holding period, the temperature is allowed to drop naturally to room temperature to obtain epoxy resin material.
[0041] The sample prepared in this embodiment has the following properties: impact strength at -40℃ 50.2 kJ / m 2 Tensile strength: 106.3 MPa; Fracture toughness: 7.6 MPa·m 1 / 2 The impact strength retention rate was 90.5% after aging at 85℃ / 85%RH for 500 hours and 85.7% after 1000 hours; the impact strength recovery rate was 85.2% after heating at 80℃ for 1 hour. The formulation parameters of this embodiment are close to the lower limit of the technical solution of the present invention. The experimental results show that even at the lowest formulation amount, the prepared material can still meet the various performance indicators required by the present invention, verifying the reliability of the technical solution of the present invention. Example 5
[0042] S1: Phenylboronic acid and epichlorohydrin were mixed at a molar ratio of 1:2.2, and 0.4% of tetrabutylammonium bromide was added as a catalyst. The mixture was reacted at 80°C for 4 hours. After the reaction was completed, 10% sodium hydroxide aqueous solution was added to neutralize the mixture. After separation, the organic phase was distilled under reduced pressure at 120°C and -0.1 MPa to remove unreacted epichlorohydrin. The measured epoxy equivalent of the obtained diglycidyl ether phenylboronic acid was 174 g / eq, and the measured boron content was 4.24 wt%.
[0043] S2: Take 100 parts by weight of bisphenol A epoxy resin E-51, 16 parts of the above-prepared phenylboronic acid diglycidyl ether ester, and 19 parts of PolyTHF 750 S and mix them evenly. Control the stirring speed at 400 rpm and the reaction temperature at 90℃. After the prepolymerization reaction is 1.75 hours, add 0.35 parts of silane coupling agent KH560 and continue the reaction for 0.5 hours. The total prepolymerization time is 2.25 hours.
[0044] S3: Add 28 parts of 1,3-cyclohexanedimethylamine and 1.0 part of accelerator 2,4,6-tris(dimethylaminomethyl)phenol to the prepolymerized system, stir and mix evenly, and then degas under vacuum at 45℃ and -0.098MPa for 15 min.
[0045] S4: Control the heating rate at 2.1℃ / min and use a three-stage gradient heating and curing method: the first stage is to heat to 88℃ and hold for 1.75 hours, the second stage is to heat to 130℃ and hold for 2.25 hours, the third stage is to heat to 160℃ and hold for 2.25 hours, and after the holding period, the temperature is allowed to drop naturally to room temperature to obtain epoxy resin material.
[0046] The sample prepared in this embodiment has the following properties: impact strength at -40℃ 53.8 kJ / m 2 Tensile strength 110.8 MPa, fracture toughness 8.0 MPa·m 1 / 2 The impact strength retention rate was 92.7% after aging at 85℃ / 85%RH for 500 hours and 87.9% after 1000 hours; the impact strength recovery rate was 88.1% after heating at 80℃ for 1 hour.
[0047] Comparative Example 1 Take 100 parts by weight of bisphenol A epoxy resin E-51, 15 parts of butyl glycidyl ether small molecule diluent, and 20 parts of common hydroxyl-terminated polytetrahydrofuran (molecular weight distribution coefficient 1.8), mix them evenly, add 30 parts of fatty amine curing agent ethylenediamine, stir and mix, then degas under vacuum, cure at 120℃ for 4 hours, and allow to cool naturally to obtain the sample. This comparative example does not contain silane coupling agent, has no dynamic covalent bond structure, and uses existing isothermal curing process.
[0048] The properties of the sample prepared in this comparative example are: impact strength at -40℃ 28.6 kJ / m 2 Tensile strength 78.3 MPa, fracture toughness 4.2 MPa·m 1 / 2 The impact strength retention rate was 62.7% after aging at 85℃ / 85%RH for 500 hours and 41.2% after aging for 1000 hours. When a 50J hammer impact was applied to the sample, visible cracks appeared but the sample did not completely break. After heating at 80℃ for 1 hour, the impact strength recovery rate was 0%.
[0049] Comparative Example 2 Take 100 parts by weight of bisphenol A epoxy resin E-51, 15 parts of butyl glycidyl ether small molecule diluent, and 20 parts of carboxyl-terminated butadiene-acrylonitrile rubber toughening agent, mix them evenly, add 30 parts of isophorone diamine, add 1 part of dynamic disulfide bond chain extender 4,4'-dithiodiphenylamine, stir and mix, then degas under vacuum, cure at 120℃ for 4 hours, and then allow to cool naturally to obtain the sample. This comparative example does not add silane coupling agent and uses existing isothermal curing process.
[0050] The properties of the sample prepared in this comparative example are: impact strength at -40℃ 39.2 kJ / m 2 Tensile strength: 85.6 MPa; Fracture toughness: 5.7 MPa·m 1 / 2 The impact strength retention rate was 71.3% after aging at 85℃ / 85%RH for 500 hours and 53.6% after aging for 1000 hours. When the sample was subjected to a 50J hammer impact, which caused visible cracks but not complete fracture, the impact strength recovery rate was 62.1% after heating at 80℃ for 1 hour.
[0051] Comparative Example 3 All raw materials and processes are completely consistent with Example 2, except that the narrow-distribution PolyTHF 750 S is replaced with a common wide-distribution terminal hydroxyl polytetrahydrofuran (number-average molecular weight 750, molecular weight distribution coefficient 1.8). This comparative example lacks the core technical characteristics of the narrow-distribution toughening component and is used to verify the toughening effect of the narrow-distribution PTHF.
[0052] The properties of the sample prepared in this comparative example are: impact strength at -40℃ 37.4 kJ / m 2 Tensile strength 82.7 MPa, fracture toughness 5.4 MPa·m 1 / 2 The impact strength retention rate was 72.5% after aging at 85℃ / 85%RH for 500 hours and 54.8% after 1000 hours; the impact strength recovery rate was 68.7% after heating at 80℃ for 1 hour. In this comparative example, the wide-distribution PTHF was prone to agglomeration, resulting in a decrease of approximately 30% in various mechanical properties compared to Example 2. This verifies that the narrow-distribution PTHF of this invention can solve the defect of reduced matrix strength due to toughening component agglomeration.
[0053] Comparative Example 4 All raw materials and formulations are completely identical to those in Example 2, except that the three-stage gradient curing is replaced with a constant temperature curing at 130℃ for 4.5 hours, with no control over the heating rate. This comparative example lacks the core technical features of gradient curing and is used to verify the homogenization effect of gradient curing. The average properties of the samples prepared in this comparative example are: impact strength at -40℃ 41.6 kJ / m 2 Tensile strength 91.3 MPa, fracture toughness 6.1 MPa·m 1 / 2 The relative standard deviation of the impact strength was 12.3%, which is much higher than the 2.1% of Example 2. In this comparative example, the large difference in crosslinking density between the inner and outer surfaces due to isothermal curing resulted in high performance fluctuations, which verifies that the gradient curing of this invention can solve the defects of uneven curing and large performance dispersion.
[0054] Comparative Example 5 All raw materials and processes are completely consistent with Example 2, except that the silane coupling agent KH560 is not added. This comparative example lacks the core technical feature of interface modification and is used to verify the weather resistance improvement effect of the silane coupling agent.
[0055] The properties of the sample prepared in this comparative example are: impact strength at -40℃ 52.1 kJ / m 2 Tensile strength 108.7 MPa, fracture toughness 7.9 MPa·m 1 / 2 The impact strength retention rate was 72.4% after aging at 85℃ / 85%RH for 500 hours and 65.8% after aging for 1000 hours; the impact strength recovery rate was 87.9% after heating at 80℃ for 1 hour.
[0056] Because this comparative example lacks interfacial bonding reinforcement, its performance degradation after aging is 2.3 times that of Example 2. This verifies that the silane coupling agent of the present invention can solve the defects of poor weather resistance caused by weak interfacial bonding and easy migration of diluent.
[0057] Performance test data table Table 1. Low-temperature mechanical property parameters of each embodiment and comparative example.
[0058] As shown in the table, the comparative data reveals that the -40℃ impact strength, tensile strength, and fracture toughness of the five embodiments are significantly higher than those of the five comparative examples. Examples 1-3 and Example 5 all meet the performance requirements of the technical specifications. Example 4 verifies the feasibility of the parameters near the lower limit, indicating that the combination of reactive diluent and narrow-distribution PTHF used in this invention effectively solves the defects of existing technologies, such as high low-temperature brittleness and reduced matrix strength while toughening. The technical solution has a wide range of applicability and high stability. The newly added comparative example 3 shows a decrease in performance due to the use of wide-distribution PTHF, and comparative example 4 shows increased performance dispersion due to the lack of gradient curing, further demonstrating the effectiveness of narrow-distribution PTHF and gradient curing in solving the corresponding defects.
[0059] Table 2. Aging resistance and self-healing performance parameters of each embodiment and comparative example.
[0060] As shown in the table, the 85℃ / 85%RH conditions used in this damp heat aging test meet the requirements of GB / T 2573-2008. The impact strength retention rate of the example with added silane coupling agent after aging is more than 30% higher than that of the comparative example without silane coupling agent. Simultaneously, the repair efficiency of dynamic boron-oxygen bonds is far higher than that of the existing dynamic disulfide bond system, effectively solving the defects of easy migration and precipitation of diluents, poor weather resistance, and low repair efficiency in existing technologies, thus improving the long-term service stability of the material. Comparative Example 5, without added silane coupling agent, showed a performance degradation rate 2.3 times that of Example 2 after aging, verifying the effectiveness of silane coupling agent in solving weather resistance defects and further supporting the necessity of the core features of the technical solution.
[0061] refer to Figure 2 This figure shows a direct comparison of the core low-temperature mechanical properties of Example 2 with three typical existing / control group samples. It can be seen that the three low-temperature properties of Example 2 are all higher than those of the three control samples. Specifically, the impact strength at -40℃ is increased by 98% compared with Comparative Example 1, 44.7% compared with Comparative Example 2, and 51.6% compared with Comparative Example 3, while the tensile strength does not decrease. This verifies that the toughening scheme of the present invention, which uses a reactive diluent and a narrow distribution PTHF compound, effectively solves the defects of the prior art, such as high low-temperature brittleness and significant reduction in matrix strength while toughening. At the same time, it eliminates the performance degradation problem caused by the agglomeration of wide distribution PTHF, which can provide mechanical performance support for the long-term service of ice and snow equipment in extreme low-temperature environments.
[0062] refer to Figure 3The 250h and 750h data used in this figure are from the same batch of tests, and are parallel experiments in the same group as the 0h, 500h, and 1000h tests disclosed in the main text, forming a complete aging performance test sequence. This figure visually presents the performance degradation trend of different samples under 85℃ / 85%RH humid heat aging environment. It can be seen that the aging performance retention rate of Example 2 is always much higher than that of the three control samples. After aging for 1000h, the retention rate still reaches 88.7%, which is 34.8% higher than that of Comparative Example 5 without silane coupling agent. This verifies that the present invention uses silane coupling agent to strengthen interfacial bonding and reactive diluent to covalently integrate into the crosslinking network. This effectively solves the defects of poor weather resistance caused by easy migration and precipitation of small molecule diluents and weak interfacial bonding in the prior art, greatly reducing the performance degradation rate of materials during long-term service and extending the service life of ice and snow equipment.
[0063] refer to Figure 4 This statistical analysis is based on the test results of five consecutive batches of production, with five samples randomly selected from each batch, ensuring a rigorous foundation for the statistical analysis of dispersion data. This figure compares the performance dispersion of five consecutive batches of products under two curing processes. It can be seen that the relative standard deviation of impact strength for all batches in Example 2 is less than 2.6%, and the performance fluctuation is only about 1 / 6 of that in Comparative Example 4. This verifies that the three-stage gradient temperature curing process used in this invention can effectively avoid the problem of uneven crosslinking density caused by large differences in crosslinking rates inside and outside the system during isothermal curing. It solves the defects of uneven curing and large batch performance dispersion in existing technologies, improves the consistency of product performance in industrial production, reduces the defect rate, and is suitable for the quality control requirements of large-scale production of ice and snow equipment.
[0064] refer to Figure 5 This experiment achieved different damage energies by adjusting the drop height of the hammer, with other conditions consistent with the main text, covering the 50J standard damage gradient used in the main text, forming a complete chain of evidence with the tests in the main text. This figure compares the repair effects of the two types of dynamic bond systems under different damage levels. It can be seen that Example 2 maintains high repair efficiency in the damage range of 30J to 70J, and even under strong impact damage of 70J, the repair efficiency still exceeds 82%, an improvement of 71.6% compared to Comparative Example 2. This verifies that the dynamic boron-oxygen bond introduced in this invention has milder triggering conditions and higher exchange activity, effectively solving the defects of low repair efficiency and poor adaptability to damage levels in existing dynamic crosslinking systems. It can achieve autonomous repair of microcracks and impact damage generated during the use of ice and snow equipment, avoiding component failure caused by damage propagation, and further improving the service safety and service life of ice and snow equipment.
[0065] refer to Figure 6This figure visually illustrates the changing trends of the two core properties of the material when the amount of reactive diluent added is in the range of 14-20 parts. Throughout the entire parameter range, the low-temperature impact strength of the material is higher than 49 kJ / m. 2 The repair efficiency was higher than 85%, with only a slight performance decrease after the addition amount exceeded the optimal range. This verifies that the formulation system of the present invention has a wide range of parameter adaptability. The addition amount can be adjusted according to the performance requirements of different ice and snow equipment, and it is suitable for multiple application scenarios such as the high rigidity requirements of figure skating shoe support components, the high toughness requirements of curling body, and the high repair requirements of ski core layer. It solves the defect of narrow adaptability of existing modified epoxy formulations and has high industry promotion value.
[0066] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for preparing high-strength and tough epoxy resin for sports ice and snow equipment via crosslinking, characterized in that, Includes the following steps: S1: Synthesize diglycidyl ether phenylborate as a reactive diluent; S2: Mix phenylborate diglycidyl ether ester, bisphenol A epoxy resin E-51, and narrow molecular weight terminal hydroxyl polytetrahydrofuran evenly, stir and react at 85~95℃ for 2~2.5 hours, and add silane coupling agent 30 minutes before the end of the reaction. S3: Add alicyclic amine curing agent and accelerator to the prepolymerized system, stir and mix evenly, and then perform vacuum degassing treatment; S4: A three-stage gradient heating and curing process is adopted, with the heating rate strictly controlled at 1.8~2.2℃ / min. The first stage is held at 85~90℃ for 1.5~2 hours, the second stage is held at 125~135℃ for 2~2.5 hours, and the third stage is held at 155~165℃ for 2~2.5 hours. After the heating is completed, the temperature is allowed to drop naturally to room temperature to obtain epoxy resin material.
2. The preparation method according to claim 1, characterized in that, The synthesis steps of phenylboronic acid diglycidyl ether ester in S1 are as follows: phenylboronic acid and epichlorohydrin are mixed at a molar ratio of 1:2.1 to 1:2.3, and 0.3% to 0.5% of tetrabutylammonium bromide by total mass is added as a catalyst. The mixture is reacted at 70 to 90°C for 3 to 5 hours. After the reaction is completed, sodium hydroxide aqueous solution is added for neutralization. After separation, the organic phase is taken and the unreacted epichlorohydrin is removed by vacuum distillation. The epoxy equivalent of the obtained phenylboronic acid diglycidyl ether ester is 165 to 185 g / eq.
3. The preparation method according to claim 1, characterized in that, The mass proportions of each raw material in S2 are as follows: 100 parts of bisphenol A epoxy resin E-51, 14-20 parts of diglycidyl ether phenylborate, 18-22 parts of narrow molecular weight terminal hydroxyl polytetrahydrofuran, and 0.2-0.5 parts of silane coupling agent.
4. The preparation method according to claim 3, characterized in that, The molecular weight distribution coefficient of the narrow molecular weight terminal hydroxyl polytetrahydrofuran does not exceed 1.2, and the number average molecular weight is 600~900.
5. The preparation method according to claim 1, characterized in that, The stirring rate of the prepolymerization reaction in S2 is 300~500 rpm, the prepolymerization temperature is 85~95℃, the prepolymerization time is 2~2.5 hours, and the silane coupling agent is added 30 minutes before the end of the prepolymerization reaction.
6. The preparation method according to claim 1, characterized in that, The silane coupling agent is any one of KH550, KH560 or KH570.
7. The preparation method according to claim 1, characterized in that, The alicyclic amine curing agent in S3 is isophorone diamine, montanane diamine, or 1,3-cyclohexanedimethylamine, with an addition amount of 20-40 parts by weight, and the accelerator is 2,4,6-tris(dimethylaminomethyl)phenol, with an addition amount of 0.5-2 parts by weight.
8. The preparation method according to claim 1, characterized in that, The vacuum degree of vacuum degassing in S3 is -0.09MPa to -0.1MPa, the degassing temperature is 40 to 50℃, and the degassing time is 10 to 20 minutes.
9. The preparation method according to claim 1, characterized in that, The prepared epoxy resin material is used to manufacture the core layer of alpine skis or the body components of ice hockey sticks. The epoxy resin material has an impact strength ≥50kJ / m at -40℃. 2 Fracture toughness ≥7.5MPa·m 1 / 2 Tensile strength ≥105MPa, and impact strength recovery rate ≥85% after heating at 80℃ for 1 hour.